2011
DOI: 10.1093/neuonc/nor036
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt inhibitory factor 1 (WIF1) is targeted in glioblastoma and has a tumor suppressing function potentially by induction of senescence

Abstract: Gene expression-based prediction of genomic copy number aberrations in the chromosomal region 12q13 to 12q15 that is flanked by MDM2 and CDK4 identified Wnt inhibitory factor 1 (WIF1) as a candidate tumor suppressor gene in glioblastoma. WIF1 encodes a secreted Wnt antagonist and was strongly downregulated in most glioblastomas as compared with normal brain, implying deregulation of Wnt signaling, which is associated with cancer. WIF1 silencing was mediated by deletion (7/69, 10%) or epigenetic silencing by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
67
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 54 publications
4
67
0
1
Order By: Relevance
“…7,8 Our study also revealed an inverse correlation between promoter methylation and WIF1 protein expression, and an increase in WIF1 mRNA and protein expression level following demethylation treatment, confirming that promoter methylation is a major inactivation mechanism of the WIF1 gene.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…7,8 Our study also revealed an inverse correlation between promoter methylation and WIF1 protein expression, and an increase in WIF1 mRNA and protein expression level following demethylation treatment, confirming that promoter methylation is a major inactivation mechanism of the WIF1 gene.…”
Section: Discussionsupporting
confidence: 71%
“…19 The main mechanism of WIF1 inactivation is aberrant promoter methylation, as demonstrated by the inverse correlation between WIF1 promoter methylation and expression of WIF1 mRNA or protein 8,11,12,[19][20][21][22][23][24] and restoration of WIF1 expression by promoter demethylation treatment. 9,20,22, 23 Yang et al 7 first described WIF1 gene promoter hypermethylation in human astrocytoma and showed that this methylation was associated with decreased Wif1 mRNA and protein expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations